The amelioration of tidal peatland to improve liberica coffee productivity in Jambi. Issue 1 (April 2021) - Ferry, Y; Putra, S; Wulandari, S
Abstract: Liberica coffee is a type of coffee that is adaptable to peatlands. The farmers in Jambi has been using peatland to grow Liberica coffee. However, after more than 15 years the productivity started to decline by 25%. This study aims to increase the productivity of Liberica coffee in tidal peat soils. The study used a randomized block design with soil ameliorants as treatments, namely (P0 as control) no ameliorants, (P1) dolomite, (P3) manure, (P4) biofertilizer, (P5) dolomite + manure, and (P6) manure + biofertilizer. Four replications were used with plot size 2 x 5 plants. The total samples of the study were 280 plants. Maintenance of the area and plants includes weeding, cleaning tertiary channels, cleaning the plant areas. Simultaneously, parameters observed, including the number of branches, number of bunch/branches, number of berries, berries production, number of berries/100 g. Vegetative parameters were the increase in plant height and number of branches. Another parameter was soil analysis. The results showed that amelioration of peatland increased nutrition in the Liberica coffee leaf. Dolomite application increased the P, Mg, and Fe levels. In contrast, manure increased N, K, and Fe, biofertilizers or dolomite combined with manure increased N, P, K, and Fe. In contrast, the combination of dolomite and biofertilizer increased P, K, and manure, and biofertilizer increased N, P, and Fe in Liberica coffee leaf. Dolomite increased plant height up to 0, 76 cm and the number of branches up to 5, 05 branches/plant of the Liberica coffee. Dolomite application also increased productivity up to 47.96%, manure 30.69%, while other soil ameliorants can increase productivity by 4.11% to 11.87%. Dolomite, manure, and biofertilizer application can improve berries quality by 5%.